National environment management action plan (NEMAP) summary. - Bangladesh. Paribe sa o Bana Mantran alaya (Dhaka NEMAP Secretariat, 1995)
Plan meant for concretizing programs and interventions aimed at promoting better management of scarce resources and reversing present trends of degradation in Bangladesh.
v.1. Summary -- v.1b. Summary in Bangla -- v.2. Main report -- v.3. Project concept papers -- v.4. Methodology -- v.5. Technical appendices.
Vol. 1 issued in English and Bengali.
At head of title: Ministry of Environment and Forest, Government of the People's Republic of Bangladesh.
Keywords: Environmental policy -- Bangladesh